Experiences with Oracle for Linux on zSeries - Arrell, Kathryn; Dutcavich, Denny; Frank, Bruce; Gorman, Michael; Jaenen, Mark; Russell, Tom (IBM redbooks., 2003)
This IBM Redbooks publication describes experiences gained while installing and testing Oracle9i for Linux on zSeries, such as: Setting up the development systems at Oracle for the Linux on zSeries environment Installing the Oracle9i instances for Linux/390 on zSeries Performing basic monitoring and tuning exercises. The book is based on real-world experiences gained by team members and technical professionals during development and early testing of this product at: The IBM Oracle EMEA Joint Solution Center, Montpellier, France The IBM Oracle International Competency Center, San Mateo, California Early customer installations Development systems at Oracle in Redwood Shores, California. This book will be of use to those customers who are using Oracle9i for Linux/390 on zSeries for the first time.